Intoxicação experimental por Pterodon emarginatus (Fabaceae) em bovinos e ovinos - Caldeira, Flávio Henrique Bravim (2013)
Pterodon emarginatus (Fabaceae) is a tree species distributed throughout the cerrado and the transition region of the Brazilian Atlantic Forest. Known popularly as "sucupira" or "faveiro", is widespread empirically by therapeutic capacity of extracts and teas beans and their hulls. This knowledge has been popular reasoned with some studies that have demonstrated anti-inflammatory and antibiotic your statement. But there are few studies about possible toxic effects of this plant. Recent studies have reported mortality after consumption of cattle from P. emarginatus. The outbreaks were usually associated with the consumption of twigs, leaves and beans after falling trees during storms. Necropsy findings and histopathological analysis of these animals revealed the case of a plant hepatotoxic. This study aimed to experimentally reproduce the disease in cattle and sheep, as well as characterize the clinical and pathological signs of intoxication and unravel some aspects of the toxicity of P. emarginatus. Were administered leaves, stems and pods, dried and crushed to 14 cattle and 13 sheep. The lowest toxic dose for cattle was 5g / kg bw for sheep and 7.5g / kg bw. The main clinical signs were lethargy and anorexia. The necropsy revealed hepatomegaly with disclosure lobular pattern and diffuse areas of hemorrhage in the subcutaneous and serous abomasum and rumen. Histologically observed centrolobular to massive hepatocellular necrosis associated with hemorrhage and congestion.